2015
DOI: 10.5114/cipp.2015.53897
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial competencies among adolescent siblings of the physically disabled

Abstract: <b>Background</b><br /> The current study examined possible prosocial benefits of having a disabled sibling. Until now research has mainly focused on the negative effects of having a sibling with a disability. We hypothesized that regular and frequent interactions with a disabled person should result in an increase of positive attitude and empathy toward other people who are in a disadvantageous situation.<br /> <br /> <b>Participants and procedure</b><br /> A sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Specifically, findings from the current study indicated that older adolescents showed significantly lower levels of offline civic behaviour than younger adolescents, which is opposite to the trend typically reported in the literature, while girls were found to report significantly higher altruistic intentions than boys. In relation to these findings, it is important to note, however, that a number of researchers have provided evidence to suggest that gender and age effects may vary depending on the type of prosocial or civic behaviour being assessed (Eberly-Lewis and Coetzee, 2015; Perenc et al., 2015). Hence, future research may benefit from further assessing age and gender differences in a variety of offline and online civic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, findings from the current study indicated that older adolescents showed significantly lower levels of offline civic behaviour than younger adolescents, which is opposite to the trend typically reported in the literature, while girls were found to report significantly higher altruistic intentions than boys. In relation to these findings, it is important to note, however, that a number of researchers have provided evidence to suggest that gender and age effects may vary depending on the type of prosocial or civic behaviour being assessed (Eberly-Lewis and Coetzee, 2015; Perenc et al., 2015). Hence, future research may benefit from further assessing age and gender differences in a variety of offline and online civic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other research has shown that the experience of being a sibling of a brother or sister with a chronic disorder other than ASD can enhance empathy and prosocial behavior. For example, two studies compared siblings of children with physical disabilities (PD) to controls and found that siblings of children with PD scored significantly higher on measures of empathy and prosocial behavior (Perenc et al, 2015;Perenc & Pęczkowski, 2018). These findings contrast with the potential negative impacts such experiences can have on mental health and remind us that the assumption that siblings automatically will experience negative outcomes sometimes is wrong.…”
mentioning
confidence: 99%
“…There is far less research on positive functioning for siblings relative to the risks (e.g., Vermaes et al, 2012). This is unfortunate, since despite the risks, the experience of having a brother or sister with a developmental or physical disability may also embed positive outcomes (Perenc et al, 2015;Shivers, 2019). In the current study, we focus on such a positive factor (i.e., siblings' prosocial behavior).…”
mentioning
confidence: 99%
“…Because the interaction between siblings is affected when one child has a disability (Knott et al, 2007), prosocial learning may also be affected. In some instances, siblings may learn caretaking skills, to take the perspective of others, and to set the needs of others above own needs (Fjermestad et al, 2019;Perenc & Pęczkowski, 2018;Perenc et al, 2015;Shivers, 2019). In other instances, siblings may be deprived of important social and prosocial interactions with their brother or sister with a disability (Kaminsky & Dewey, 2001;Knott et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation